THE STRUGGLE OF THE SIBERIAN KYRGYZS AGAINST THE RUSSIANS AND MONGOLS IN XVIII CENTURY - O., Karatayev (Journal of history, 2018)
This study deals with the life and legacy of Erenak bek, who was a prominent Kyrgyz personality lead of a Siberian Kyrgyz circa the 17th century. Erenak bek is the third son of eminent Kyrgyz ruler İshşey Mergen, grandson of Nomchu bek who ruled the Altısar tribe which was a part of Kyrgyz state along the Yenisey River. According to the old written records, he descended from noble Kyrgyz lineage. Obviously, Erenak bek is united the Siberian Kyrgyz in the second period of the 17th century. Therefore, it could be said that Erenak bek, gathered together the Kyrgyz and their Kyshtyms (depended tribes) under one authority with the political support of Dzungar Khan Senge-Taysha and his successor Galdan Boşoktu Khan. Together, they conducted some effective operations against Russians envasion into Siberia and took some advantages from them.